Comparison of procedures to estimate critical headways at roundabouts - Vasconcelos, Luís (2013)
The capacity analysis of roundabouts in Portugal is mostly done using the UK regression method. Due to its empirical and non-explanatory nature, this method has some limitations, particularly for studying innovative layouts, which has recently motivated research in Portugal into the use of capacity methods based on gap-acceptance theory. This paper describes the results of a related project: the estimation of critical headways and follow-up times at Portuguese roundabouts. For this study, gap-acceptance data were collected at six roundabouts, in two cities, and used to estimate the parameters at each entry, for the left and right entry lanes independently. Several estimation methods were used (Siegloch, Raff, Wu, Maximum Likelihood and Logit). The results have revealed important specificities of the methods that have significant effects on the results and therefore on the capacity estimate exercises. The comparison of the estimates with reference values from several countries indicates significant differences, suggesting the existence of relevant driving style differences, which implies that locally calibrated, country-specific, parameters are required for capacity calculations.